The Effect of Motivation, Organizational Culture, Competency on Work Commitment and Performance of SD Teachers in Bengkalis District - Muhrodin, Muhrodin; Sudarno, Sudarno; Junaedi, Achmad Tavip; Andi, Andi; Putri, Novita Yulia (Interconnection: An Economic Perspective Horizon, 2024)
This study was conducted to determine and analyze the influence of motivation, organizational culture, and competence on work commitment and performance of elementary school teachers in Bengkalis District. This study was chosen because there were phenomena and problems related to the level of job satisfaction and performance of elementary school teachers in the Bengkalis District which were still low, there were many factors that influenced the high job satisfaction and performance, but the author had a temporary assumption that motivational factors, organizational culture and competence affected job satisfaction, as well as motivation, organizational culture, competence and job satisfaction affect the performance of elementary school teachers in Bengkalis District. The method used in collecting data in this research is a questionnaire. The population in this study were all elementary school civil servant teachers in Bengkalis District, amounting to 626 with a saturated sample of 626 respondents. By distributing a questionnaire using a Google form filled in by all primary school civil servants in Bengkalis District, with a total of 626 respondents, it was tested with SEM AMOS. The test results showed that motivation on job satisfaction had a positive effect, organizational culture on job satisfaction had a positive effect, competence on work commitment had a positive effect, work motivation on teacher performance has a positive effect, organizational culture on performance has a positive effect, competence on performance has no effect, work commitment on performance has no effect.